Medical titanium alloy surface bionic multifunctional composite coating and preparation method thereof

By combining micro-arc oxidation and anodizing, a cauliflower-like nanoparticle coating with a multi-level structure is prepared, which solves the existing problems of single micro-nano composite structure morphology and poor controllability on the surface of medical titanium alloys. High biological functionality and damage resistance achieved.

CN119352129APending Publication Date: 2025-01-24TAIZHOU UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411783876.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art When preparing the micro-nano composite structure of medical titanium alloy surface, the morphology is single and the controllability of the nanoscale morphology is poor, and it is easy to cause structural collapse and damage when external forces are damaged, making it difficult to provide effective antibacterial, promote angiogenesis and Bone integration function.

Method used

A bionic multifunctional composite coating on the surface of medical titanium alloy was prepared by combining micro-arc oxidation and anodizing. Micro-arc oxidation generates a micron porous coating, and anodizing synthesizes a nano-coating on its surface. By adjusting the electrolyte composition and process parameters, a cauliflower-like nanoparticle coating with a multi-level structure is formed.

Benefits of technology

It is possible to improve the biological function while maintaining the micron porous structure, enhance the antibacterial ability of the implant, promote angiogenesis and osseointegration, and have good wear resistance, corrosion resistance and resistance to external damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352129A_ABST
    Figure CN119352129A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biological material surface modification, and discloses a medical titanium alloy surface bionic multifunctional composite coating and a preparation method thereof. According to the method, the medical titanium alloy is sequentially subjected to micro-arc oxidation and anodic oxidation, and then the bionic multifunctional composite coating on the surface of the medical titanium alloy is prepared. The purpose of micro-arc oxidation is to prepare a micron porous coating on the surface of the medical titanium alloy. According to anodic oxidation, a series of nano-coatings are synthesized on the surface of the micro-arc oxidation coating, the nano-coatings can be composed of discontinuous cauliflower-shaped nano-particles or can be of a continuous film-forming cauliflower-shaped structure, and the thickness of the nano-coatings can be from the nanometer level to the micrometer level. According to the coating, the biological function is further improved through the nano coating while the mechanical anchoring effect of the micron porous structure on new bone tissue is maintained. Even if the coating is damaged by external force, the high binding force of the coating does not cause the failure of the coating, and the coating also has good wear resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomaterial surface modification, and in particular to a bionic multifunctional composite coating on the surface of a medical titanium alloy and a preparation method thereof. Background Art

[0002] Natural bone tissue has the structural characteristics of micro / nano multi-level composites, and a large number of studies have also shown that artificial bionic micro / nano composite structures can better promote bone integration than single structures. In addition, considering the complexity of the implant's action process, it is particularly important to make it have antibacterial, angiogenesis-promoting, osteogenesis-promoting, and immunomodulatory functions through appropriate surface modification. Therefore, the development of implants with micro-nano bionic multifunctional composite coatings is considered to be one of the potential ways to improve the success rate of implants.

[0003] Electrochemical surface treatment processes are widely used due to their simple process / equipment, low cost, and suitability for large-size / complex shape processing. Among them, micro-arc oxidation (MAO) uses a pulsed power supply to prepare a micron-porous coating on the surface of medical titanium alloys. The porous coating can enhance bone integration through mechanical anchoring with new bone tissue. Adding functional cations, anions, and other insoluble additives to the micro-arc oxidation electrolyte can adjust the composition of the coating, thereby regulating the functional ion release behavior and biological behavior of the coating.

[0004] Anodizing is a method of treating metal components using a DC regulated power supply. Anodizing of medical titanium surface generally refers to the process of preparing nanotube / pore structures on its surface. Nanostructures are believed to better regulate the release of functional ions, and such structures themselves also help improve the biological functions of implants.

[0005] Existing surface modification research mainly focuses on hydrothermal treatment and annealing of micro-arc oxidation coatings to grow nanorod-like structures, or sandblasting and pickling of medical titanium to produce micron-scale structures, followed by anodization to prepare nanotube structures, thereby obtaining micro-nano composite structures. The micro-nano coatings prepared by this process have a relatively simple morphology and poor controllability of the nanoscale morphology, and have obvious shortcomings when resisting external damage, which can easily cause the collapse and destruction of the entire nanostructure.

[0006] Therefore, how to perform appropriate surface modification on implants to provide micro-nano bionic coatings that can resist external damage plays an important role in the wide application of implants. Summary of the invention

[0007] The purpose of the present invention is to provide a bionic multifunctional composite coating on the surface of a medical titanium alloy and a preparation method thereof, so as to solve the above-mentioned problems existing in the coating prepared by the prior art.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, comprising the following steps:

[0010] The medical titanium alloy is subjected to micro-arc oxidation and anodic oxidation in sequence, thereby completing the preparation of the bionic multifunctional composite coating on the surface of the medical titanium alloy;

[0011] Wherein, the electrolyte of the micro-arc oxidation comprises sodium β-glycerophosphate, calcium acetate and water;

[0012] The electrolyte for anodization comprises ammonium fluoride, ethylene glycol and water.

[0013] Preferably, in the above-mentioned method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, the concentration of sodium β-glycerophosphate in the micro-arc oxidation electrolyte is 0.01 to 0.1 mol / L; the concentration of calcium acetate in the micro-arc oxidation electrolyte is 0.1 to 1 mol / L.

[0014] Preferably, in the above-mentioned method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, the mass concentration of ammonium fluoride in the anodizing electrolyte is 0.05 to 0.5 mol / L.

[0015] Preferably, in the above-mentioned method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, in the anodized electrolyte, the volume of ethylene glycol is 90-98% of the total volume of the electrolyte; and the volume of water is 2-10% of the total volume of the electrolyte.

[0016] Preferably, in the above-mentioned method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, the parameters of the micro-arc oxidation are: the current density is 0.1 to 3 A / cm 2 ; Frequency is 500~1000Hz; Duty cycle is 10~50%; Time is 1~10min.

[0017] Preferably, in the above-mentioned method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, the parameters of the anodizing are: voltage of 5 to 150 V; temperature of 25 to 60° C.; and time of 10 s to 180 min.

[0018] Preferably, in the above-mentioned method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, the medical titanium alloy further includes a pretreatment before use; the pretreatment is polishing and / or ultrasonic cleaning.

[0019] Preferably, in the above-mentioned method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, ultrasonic cleaning is also included after the micro-arc oxidation is completed; and ultrasonic cleaning is also included after the anodization is completed.

[0020] The invention also provides a method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, and obtains a bionic multifunctional composite coating on the surface of a medical titanium alloy.

[0021] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The preparation process of the bionic multifunctional composite coating of the present invention includes two steps: micro-arc oxidation and anodic oxidation. The purpose of micro-arc oxidation is to prepare a micron porous coating on the surface of the medical titanium alloy. The anodic oxidation process is to synthesize a series of nano-coatings on the surface of the micro-arc oxidation coating. Depending on the different anodic oxidation process parameters, such as voltage, F - Concentration, pH, water content, ethylene glycol content, etc. The nano coating can be composed of discontinuous cauliflower-like nanoparticles or a continuous film-forming cauliflower-like structure, and the thickness can range from nanometers to submicron or even micron levels.

[0023] (2) The biomimetic multifunctional composite coating of the present invention further improves the biological function through the nano-coating while maintaining the mechanical anchoring effect of the micron porous structure on the new bone tissue. Even when damaged by external forces, the high bonding force of the coating will not cause the coating to fail, and it also has good wear resistance and corrosion resistance.

[0024] (3) The bionic multifunctional composite coating of the present invention can be loaded with functional ions during the micro-arc oxidation stage or the anodizing stage, and synergizes with the micropores of the micro-arc oxidation coating and the honeycomb micro-nanostructure obtained by anodizing, thereby increasing the specific surface area while improving the wettability of the implant, which is beneficial to the controllable loading and release of functional drugs; and the multi-level structure is also more conducive to improving the bone integration between the new bone and the implant, thereby improving the implant success rate, and has great application prospects.

[0025] (4) The preparation method of the present invention uses simple equipment, has adjustable geometric parameters, is convenient, has strong adaptability to the shape and size of medical titanium alloy implants, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0027] Figure 1The microscopic morphology of the bionic multifunctional composite coating prepared in Example 1; wherein (a) is the microscopic morphology at a scale of 5 μm; (b) is the microscopic morphology at a scale of 500 nm; (c) is the microscopic morphology at a scale of 100 nm;

[0028] Figure 2 The microscopic morphology of the bionic multifunctional composite coating prepared in Example 2; (a) is the microscopic morphology at a scale of 5 μm; (b) is the microscopic morphology at a scale of 500 nm; (c) is the microscopic morphology at a scale of 100 nm;

[0029] Figure 3 The microscopic morphology of the bionic multifunctional composite coating prepared in Example 3; (a) is the microscopic morphology at a scale of 5 μm; (b) is the microscopic morphology at a scale of 500 nm; (c) is the microscopic morphology at a scale of 100 nm;

[0030] Figure 4 The microscopic morphology of the bionic multifunctional composite coating prepared in Example 4; (a) is the microscopic morphology at a scale of 5 μm; (b) is the microscopic morphology at a scale of 500 nm; (c) is the microscopic morphology at a scale of 100 nm;

[0031] Figure 5 The microscopic morphology of the bionic multifunctional composite coating prepared in Example 5; (a) is the microscopic morphology at a 5 μm scale; (b) is the microscopic morphology at a 500 nm scale; (c) is the microscopic morphology at a 100 nm scale. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, comprising the following steps:

[0033] The medical titanium alloy is subjected to micro-arc oxidation and anodization in sequence to complete the preparation of the bionic multifunctional composite coating on the surface of the medical titanium alloy.

[0034] In the present invention, the medical titanium alloy further includes pretreatment before use; the pretreatment is preferably polishing and / or ultrasonic cleaning; the ultrasonic cleaning is ultrasonic cleaning using anhydrous ethanol and water in sequence. The present invention does not limit the conditions for polishing and ultrasonic cleaning, and the conventional selection by those skilled in the art is sufficient.

[0035] In the present invention, the electrolyte of the micro-arc oxidation preferably includes sodium β-glycerophosphate, calcium acetate and water.

[0036] In the present invention, the electrolyte of the micro-arc oxidation preferably also includes an inorganic salt containing functional ions or a powder containing functional ions, and more preferably one or more of Cu inorganic salts, Cu nanoparticles, Ag inorganic salts, Ag nanoparticles, Sr inorganic salts, and Sr nanoparticles. The functional ions of the present invention can be selected as Cu, Ag, Sr, etc., and the functional ions are added to the electrolyte in the form of inorganic salts or nanoparticles, and then deposited into the coating through micro-arc oxidation, wherein Cu has the function of antibacterial and promoting angiogenesis, Ag can be antibacterial, and Sr can promote osteogenesis.

[0037] In the present invention, the concentration of sodium β-glycerophosphate in the micro-arc oxidation electrolyte is preferably 0.01 to 0.1 mol / L, more preferably 0.02 to 0.05 mol / L, and more preferably 0.02 mol / L; the concentration of calcium acetate in the micro-arc oxidation electrolyte is preferably 0.1 to 1 mol / L, more preferably 0.1 to 0.6 mol / L, and more preferably 0.2 mol / L.

[0038] In the present invention, the parameters of the micro-arc oxidation are: the current density is preferably 0.1 to 3 A / cm 2 , more preferably 0.2 to 1 A / cm 2 , more preferably 0.3A / cm 2 The frequency is preferably 500 to 1000 Hz, more preferably 600 to 900 Hz, and more preferably 800 Hz; the duty cycle is preferably 10 to 50%, more preferably 20 to 40%, and more preferably 30%; the time is preferably 1 to 10 min, more preferably 3 to 8 min, and more preferably 5 min.

[0039] In the present invention, the anode of the micro-arc oxidation is preferably a medical titanium alloy, and the cathode is preferably a stainless steel electrolytic cell.

[0040] In the present invention, the micro-arc oxidation further includes ultrasonic cleaning after completion; the solution for the ultrasonic cleaning is water. The present invention does not limit the conditions for ultrasonic cleaning, and the conventional selection by those skilled in the art is sufficient.

[0041] In the present invention, the electrolyte for anodization preferably includes ammonium fluoride, ethylene glycol, and water.

[0042] In the present invention, the mass concentration of ammonium fluoride in the anodizing electrolyte is preferably 0.05 to 0.5 mol / L, more preferably 0.1 to 0.3 mol / L, and more preferably 0.15 mol / L.

[0043] In the present invention, in the electrolyte for anodizing, the volume of ethylene glycol is preferably 90-98% of the total volume of the electrolyte, further preferably 93-95%, and more preferably 95%; the volume of water is preferably 2-10% of the total volume of the electrolyte, further preferably 5-7%, and more preferably 5%.

[0044] In the present invention, the parameters of the anodization are: the voltage is preferably 5-150V, more preferably 10-120V, more preferably 90V; the temperature is preferably 25-60°C, more preferably 25-40°C, more preferably 25°C; the time is preferably 10s-180min, more preferably 20-90min, more preferably 60min.

[0045] In the present invention, the anode of the anodic oxidation is preferably a medical titanium alloy that has been subjected to micro-arc oxidation, and the cathode is preferably a platinum sheet electrode.

[0046] In the present invention, after the anodization is completed, ultrasonic cleaning is also included; the solution for the ultrasonic cleaning is water. The present invention does not limit the conditions for ultrasonic cleaning, and the conventional selection by those skilled in the art can be sufficient.

[0047] In the present invention, the anodic oxidation is essentially the ammonium fluoride, F in the ethylene glycol electrolyte - The process of reacting with hydroxyapatite (HA) in the micro-arc oxidation coating to form fluoroapatite (FA). Compared with the HA coating, FA dissolves more slowly in body fluids and is less likely to cause implant failure and bone failure. This is mainly due to the fact that F - Compared with hydroxyl (OH-) which has a smaller radius, F - The incorporation of FA reduces the HA lattice constant and improves the crystal stability, thus reducing its solubility in the human body. In addition, FA also has a certain antibacterial effect, which also plays a positive role in preventing bacterial infections.

[0048] The invention also provides a method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, and obtains a bionic multifunctional composite coating on the surface of a medical titanium alloy.

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] This embodiment provides a method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, comprising the following steps:

[0052] (1) The medical titanium alloy workpiece was ground and polished, and ultrasonically cleaned with anhydrous ethanol and deionized water to remove organic and inorganic pollutants to obtain a clean surface;

[0053] (2) The polished medical titanium alloy workpiece was used as the anode and the stainless steel electrolytic cell was used as the cathode for micro-arc oxidation. The electrolyte was a mixture of sodium β-glycerophosphate, calcium acetate, and water. The concentration of sodium β-glycerophosphate was 0.02 mol / L and the concentration of calcium acetate was 0.2 mol / L. The micro-arc oxidation selected the constant current mode with a current density of 0.3 A / cm 2 , frequency 800 Hz, duty cycle 30%, time 5 min, to prepare a micron-pore coating on the surface of a medical titanium alloy workpiece; the sample after micro-arc oxidation was ultrasonically cleaned with deionized water to remove electrolyte residues, to obtain a sample with a micro-arc oxidation coating;

[0054] (3) The sample with the micro-arc oxidation coating was used as the anode and the platinum electrode was used as the cathode. A DC regulated power supply was selected for anodization. The process parameters were: the electrolyte was a mixture of ammonium fluoride, ethylene glycol, and water, the mass concentration of ammonium fluoride in the electrolyte was 0.15 mol / L, the volume of ethylene glycol was 95% of the total volume of the electrolyte, the volume of water was 5% of the total volume of the electrolyte, the temperature was 25°C, the voltage was 10V, and the time was 60min. After the anodization was completed, the sample was taken out and ultrasonically cleaned with deionized water to remove the residual electrolyte on the surface, thereby obtaining a medical titanium alloy implant with a bionic multifunctional composite coating on the surface.

[0055] After testing, the contact angle of the micro-arc oxidation coating in step (2) was 56.3°; the contact angle of the bionic multifunctional composite coating in step (3) was 29.9°.

[0056] Figure 1 The microscopic morphology of the bionic multifunctional composite coating prepared in Example 1. Figure 1 It can be seen that a layer of discontinuous cauliflower-like nanoparticles with a particle size of 20 to 30 nm has grown uniformly on the surface of the micropore wall. The wettability test results show that the introduction of the discontinuous nanoparticle coating reduces the contact angle of the micro-arc oxidation coating from 56.3° to 29.9°, showing better wettability.

[0057] The results of CCK-8 osteoblast activity test showed that compared with micro-arc oxidation coating, the osteoblast activity on the surface of bionic multifunctional composite coating increased by more than 30%.

[0058] Example 2

[0059] This embodiment provides a method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy. For details, refer to Example 1, except that the voltage of the anodizing in step (3) is adjusted to 30V, and the other conditions are the same as those in Example 1.

[0060] Figure 2 The microscopic morphology of the bionic multifunctional composite coating prepared in Example 2. Figure 2 It can be seen that a layer of discontinuous cauliflower-like nanoparticles grows uniformly on the surface of the micropore wall. The large cauliflower is composed of single or multiple small cauliflowers. The particle size of the large cauliflower is about 50nm, which is significantly larger than that under the 10V anodization voltage. The wettability test results show that the water contact angle of the bionic multifunctional composite coating reaches 12.8°, showing excellent wettability.

[0061] The results of CCK-8 osteoblast activity test showed that compared with micro-arc oxidation coating, the osteoblast activity on the surface of bionic multifunctional composite coating increased by more than 50%.

[0062] Example 3

[0063] This embodiment provides a method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy. For details, refer to Example 1, except that the voltage of the anodizing in step (3) is adjusted to 60V, and the other conditions are the same as those in Example 1.

[0064] Figure 3 The microscopic morphology of the bionic multifunctional composite coating prepared in Example 3. Figure 3 It can be seen that the surface of the micropore wall is evenly covered with a continuous coating composed of cauliflower-like nanoparticles, but there are still small gaps between the particles. The wettability test results show that the water contact angle of the bionic multifunctional composite coating reaches 9.8°, showing good wettability.

[0065] The results of CCK-8 osteoblast activity test showed that compared with micro-arc oxidation coating, the osteoblast activity on the surface of bionic multifunctional composite coating increased by more than 35%.

[0066] Example 4

[0067] This embodiment provides a method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy. For details, refer to Example 1, except that the voltage of the anodizing in step (3) is adjusted to 90V, and the other conditions are the same as those in Example 1.

[0068] Figure 4 The microscopic morphology of the bionic multifunctional composite coating prepared in Example 4. Figure 4It can be seen that the surface of the micropore wall is evenly covered with a continuous coating composed of cauliflower-like nanoparticles. The gaps between the particles still exist, but the size of the small cauliflower monomers increases significantly at low anodizing voltage. The wettability test results show that the water contact angle of the biomimetic multifunctional composite coating reaches 10.2°, showing excellent wettability.

[0069] The results of CCK-8 osteoblast activity test showed that compared with micro-arc oxidation coating, the osteoblast activity on the surface of bionic multifunctional composite coating increased by more than 50%.

[0070] Example 5

[0071] This embodiment provides a method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy. For details, refer to Example 1, except that the voltage of the anodizing in step (3) is adjusted to 120V, and the other conditions are the same as those in Example 1.

[0072] Figure 5 The microscopic morphology of the bionic multifunctional composite coating prepared in Example 5. Figure 5 It can be seen that the micropore wall is still covered by a uniform and continuous coating composed of cauliflower-like nanoparticles, but the size of the cauliflower monomer continues to increase and become more protruding. The wettability test results show that its water contact angle reaches 26.6°, showing good wettability.

[0073] The results of CCK-8 osteoblast activity test showed that compared with micro-arc oxidation coating, the osteoblast activity on the surface of bionic multifunctional composite coating increased by more than 40%.

[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy, characterized in that: The following steps are involved: The medical titanium alloy is subjected to micro-arc oxidation and anodic oxidation in sequence, thereby completing the preparation of the bionic multifunctional composite coating on the surface of the medical titanium alloy; Wherein, the electrolyte of the micro-arc oxidation comprises sodium β-glycerophosphate, calcium acetate and water; The electrolyte for anodization comprises ammonium fluoride, ethylene glycol and water.

2. The method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy according to claim 1, characterized in that: The concentration of β-sodium glycerophosphate in the electrolyte of the micro-arc oxidation is 0.01-0.1 mol / L; the concentration of calcium acetate in the electrolyte of the micro-arc oxidation is 0.1-1 mol / L.

3. The method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy according to claim 2, characterized in that: In the electrolyte for anodizing, the mass concentration of ammonium fluoride is 0.05-0.5 mol / L.

4. The method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy according to claim 3, characterized in that: In the electrolyte for anodic oxidation, the volume of ethylene glycol is 90-98% of the total volume of the electrolyte; the volume of water is 2-10% of the total volume of the electrolyte.

5. The method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy according to claim 2 or 3, characterized in that: The parameters of the micro-arc oxidation are: current density is 0.1-3A / cm 2 ; Frequency is 500~1000Hz; Duty cycle is 10~50%; Time is 1~10min.

6. The method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy according to claim 5, characterized in that: The parameters of the anodizing are: voltage of 5 to 150 V; temperature of 25 to 60° C.; and time of 10 s to 180 min.

7. The method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy according to claim 1 or 3, characterized in that: The medical titanium alloy further includes pretreatment before use; the pretreatment is polishing and / or ultrasonic cleaning.

8. The method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy according to claim 7, characterized in that: After the micro-arc oxidation is completed, ultrasonic cleaning is also included; after the anodization is completed, ultrasonic cleaning is also included.

9. A bionic multifunctional composite coating on the surface of a medical titanium alloy obtained by the method for preparing a bionic multifunctional composite coating on the surface of a medical titanium alloy as described in any one of claims 1 to 8.

Citation Information

Cited By

  • Medical titanium alloy surface modification coating for bone implantation

    CN120844172A

  • Preparation method and application of medical implant

    CN121023608A

  • Method for producing a medical implant and use thereof

    CN121023608B